STRATEGI PENYUSUNAN DAN PENYESUAIAN STRUKTUR ORGANISASI YAYASAN - Ali Mustofa; Khoirul Anwar; Gunawan; H. Ahd Fauzi; Zaini Najih Karimi (Fakultas Agama Islam Universitas Wiralodra, 2022)
STRATEGY FOR DEVELOPMENT AND ADJUSTMENT OF THE FOUNDATION ORGANIZATIONAL STRUCTURE The organizational structure of a foundation is a description or arrangement that contains the division of authority and responsibility along with vertical and horizontal relationships within a foundation in carrying out its duties. The organizational structure must be made through the correct stages. This is done so that the foundation organization can run easily in achieving its goals. This organizational structure must also be made in a structured and appropriate manner between tasks and members in the organization so that it can run optimally. In addition, with a good and correct organizational structure, over time the organization of the foundation will experience development with the expansion of the organization becoming more complex. This is triggered by foundations that are permitted by law to establish business entities with the aim of supporting the foundation's own goals, and not for profit. Thus, the strategy for compiling and adjusting the organizational structure of a foundation can be said to be a strategy that is indispensable for the sustainability of a foundation organization itself.